A Chinese mitten crab Eriocheir sinensis from the River Clyde – the first record of this invasive, non-native species in Scotland. Issue 1 (December 2016) - Yeomans, William; Clark, John
Abstract The remains (probably a moult) of a female Chinese mitten crab were found in the freshwater River Clyde. This is the first report of a Chinese mitten crab from the wild in Scotland and is well outside the previously recorded range of the species in Great Britain. The origin of this specimen remains enigmatic but this finding has potentially serious implications for the Clyde catchment, the biota of which is recovering from centuries of poor water quality and structural modification. Work is now required to determine whether the Clyde has been colonised by the Chinese mitten crab and, if so, to establish the size of the resident population, its associated threat to local biodiversity and the implications for river management under the European Union Water Framework Directive.